Needs Analysis Blended Laboratory in The Context of the Adequacy of Supporting Facilities for Science Learning Using the Internet of Things and Augmented Reality - Dadan Rosana (Universitas Negeri Yogyakarta, 2021)
The blended laboratory model in this study refers to an integrated laboratory concept combining synchronous (real laboratory activities) using the Internet of things (IoT) and asynchronous learning with augmented reality (AR). The application of blended laboratory model in science learning teachers is still low in Indonesia due to the lack of ICT support for online learning. This preliminary study was conducted to analyze the need for the development of the blended laboratory model with IoT and AR involving 45 science teachers and 42 junior high school students as the respondents with stratified random sampling technique. The research method employed survey and focus group discussion. The results of the study showed that (1) 67% of teachers and 92% of students have never used AR, (2) 72% of teachers and 89% of students have never utilized IoT, (3) 65% of science laboratories in the junior high school do not have proper devices for AR application, (5) 76% of science laboratories in the junior high schools are not facilitated with proper equipment for the IoT application, (6) the respondents stated that the development of blended laboratory is very important (72%) and important (18%) to support IT-based learning, especially to deal with the conditions after the Covid-19 outbreak. ©2021 JSER. Universitas Negeri Yogyakarta